2003
DOI: 10.1523/jneurosci.23-10-04270.2003
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin Differentially Modulates Non-NMDA Receptors in Vasopressin and Oxytocin Neurons in the Supraoptic Nucleus

Abstract: Magnocellular neurons of the supraoptic nucleus release the neuropeptides oxytocin and vasopressin from their dendrites to regulate their synaptic inputs. This study aims to determine the cellular mechanism by which vasopressin modulates excitatory synaptic transmission. Presumably by electroporation through perforated patch, we were able to successfully introduce biocytin into cells in which we performed an electrophysiological study. This method enabled us to determine that roughly half of the recorded neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 49 publications
1
65
0
Order By: Relevance
“…Likewise, vasopressin (VP) cells can release VP (Pow and Morris, 1989) or dynorphin (Watson et al, 1982). These molecules have all been shown previously to modulate neurotransmission in the PVN or supraoptic nucleus (Brussaard et al, 1996;Kombian et al, 1997;Hirasawa et al, 2003;Oliet et al, 2007). Although the vast majority of EPSCs recorded in MNCs displayed synchronous followed by asynchronous release, we did record EPSCs in some cells that displayed robust asynchronous release with little synchronous component.…”
Section: Prolonged Epsps In Mncs Results From Asynchronous Glutamate Rmentioning
confidence: 87%
“…Likewise, vasopressin (VP) cells can release VP (Pow and Morris, 1989) or dynorphin (Watson et al, 1982). These molecules have all been shown previously to modulate neurotransmission in the PVN or supraoptic nucleus (Brussaard et al, 1996;Kombian et al, 1997;Hirasawa et al, 2003;Oliet et al, 2007). Although the vast majority of EPSCs recorded in MNCs displayed synchronous followed by asynchronous release, we did record EPSCs in some cells that displayed robust asynchronous release with little synchronous component.…”
Section: Prolonged Epsps In Mncs Results From Asynchronous Glutamate Rmentioning
confidence: 87%
“…We examined GABA A receptor-mediated transmission in AVP neurons identified with electrophysiological characteristics 30,31 or post hoc immunohistochemical analysis. 30 In most of the identified AVP neurons, E GABA was negative to the action potential threshold (which was ≈−45 mV), and the GABA A receptor agonist muscimol decreased the firing rate by causing hyperpolarization. These findings indicate that GABA is inhibitory in most AVP neurons as has been reported in most previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the putative AVP neurons, sampled from the SON or the lateral magnocellular subnucleus of the PVN, exhibited the electrophysiological characteristics of AVP neurons, 30,31 including phasic firing patterns ( Figure 1A), with little or no inward rectification at membrane potentials between −50 and −130 mV ( Figure 1B). After recordings, immunohistochemical analysis ( Figure 1C) confirmed that the cells that exhibited the physiological signature of AVP neurons did express AVP neurophysin (21 of 23 cells from 7 rats).…”
Section: Identification Of Avp Neuronsmentioning
confidence: 99%
“…AVP, however, also has significant actions at central oxytocin receptors as well (Hirasawa et al, 2003). The V1a antagonist SR49059 possesses little activity at central oxytocin receptors (Manning et al, 1993).…”
Section: V1a Receptors Tonically Depress Release Probabilitymentioning
confidence: 99%